Sources on the history of monasteries of the Nizhny Novgorod Diocese in the XVIII century: types and characteristics of information potentials - A. D. Averkiev (Омский научный вестник: Серия "Общество. История. Современность")
The article provides a detailed description of archival historical sources about the life, economic activity and daily life of the monasteries of the Nizhny Novgorod diocese in the XVIII century. The relevance of the study is to expand the understanding of the information potential of insufficiently studied archival funds on this issue. The theoretical basis of the research is a combination of an institutional approach, the principle of consistency and a comparative historical method. This methodological set made it possible, by identifying and processing the sources, to establish that the transformations in the church structure radically changed the nature and types of historical sources containing information about the administration, economy and internal life of monasteries.